ADOLESCENT’S ATTITUDE TOWARD GOVERNMENT REGULATION NO. 23 2002 ABOUT CHILDREN PROTECTION - Resti Febriyanti; Adelina Hasyim; Hermi Yanzi (FKIP Unila, 2013)
This research aimed to analyze and explain about the level of knowledge, emotional tendency, and tendency of act of adolescent in SMK Kartikatama I Metro Selatan Kota Metro toward government regulation no. 23 2002 about children protection and describe the message of government regulation no. 23 2002 about children protection. The research used descriptive qualitative research methods with the samples are 95 respondents. The main technique of data collecting used a questionnaire with attitude scale and to analyze the collected data, it is used percentage formula. Hasil penelitian menunjukkan bahwa sikap remaja terhadap ketentuan Undang-Undang Nomor 23 Tahun 2002 tentang perlindungan anak di kelas X SMK Kartikatama I Metro Selatan Kota Metro untuk indikator kognisi atau tingkat pengetahuan adalah 51% atau 48 responden dari 95 repsonden cukup baik mengenai ketentuan Undang-Undang Nomor 23 Tahun 2002 tentang perlindungan anak. Untuk indikator afeksi atau kecenderungan emosional 53,7% atau 51 responden dari 95 responden remaja setuju mengenai ketentuan Undang-Undang Nomor 23 Tahun 2002 tentang perlindungan anak. Dan untuk indikator konatif atau kecenderungan bertindak, 51,6% atau 49 responden mendukung ketentuan Undang-Undang Nomor 23 Tahun 2002 tentang perlindungan anak.KATA KUNCI: Sikap, Remaja, Undang-Undang Nomor 23 Tahun 2002, Perlindungan Anak